CUSTOMER ACCEPTANCE OF 4G - WIMAX SERVICE OF BSNL IN KOTTAYAM KERALA - Sabu M. Yohannan (International Journal in Management and Social Science, 2014)
Communication is necessitated as a need for the present era. It makes the common life more meaningful and faster. Apart from voice communication, data communication is more to be addressed now a days. An ideal data communication service assures high data transfer rate, uninterrupted connectivity, affordable tariff and good service support. In this study “Customer acceptance of 4G - WiMAX service of BSNL in Kottayam Kerala.”, the researcher analyses the Customer acceptance of latest 4G based WiMAX data service of BSNL -a renowned telecom service provider of allover India. Data are collected from 152 respondents in Kottayam District, Kerala. and their acceptance is analyzed using statistical tools like percentage analysis, Chi-square test, T-test and F-test with respect to various Technical factors of WiMAX service and Personal factors of customers.